2016
DOI: 10.1007/s12063-016-0112-1
|View full text |Cite
|
Sign up to set email alerts
|

The organizational infrastructure of continuous improvement – an empirical analysis

Abstract: To pursue constant incremental improvements, firms must develop the dynamic capability of continuous improvement (CI). Research suggests that an organizational infrastructure is necessary to sustain CI capability. Although there have been some attempts to delineate a comprehensive model for CI infrastructure, empirical investigation is still underdeveloped. The present study explores key dimensions of the organizational infrastructure-strategic alignment, teamwork for problem solving, and goals management syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 91 publications
3
62
0
Order By: Relevance
“…Researchers assert the need to engage personnel in CI through design of the appropriate rewards and recognition system for employees that participate in CI projects (Sabella et al, 2014;Yang et al, 2014;Habtoor, 2016). To ensure strategic alignment of CI and its ability to achieve declared goals, it is important to develop a system of goals for the improvement initiative (Kaynak, 2003;Sabella et al, 2014;Galeazzo et al, 2016). The latent variable of CI is evaluated in three dimensions: the company's strive for quality improvement (operationalized from Prajogo and Brown 2006, Sila (2007), and Näslund (2013)) and on-going elimination of nonvalue added activities (from Deming (1993) and Jurburg et al, (2015)) as well as process standardization (from Pellicer et al, (2012) and Romero et al (2015)).…”
Section: Soft and Hard Organizational Practicesmentioning
confidence: 99%
“…Researchers assert the need to engage personnel in CI through design of the appropriate rewards and recognition system for employees that participate in CI projects (Sabella et al, 2014;Yang et al, 2014;Habtoor, 2016). To ensure strategic alignment of CI and its ability to achieve declared goals, it is important to develop a system of goals for the improvement initiative (Kaynak, 2003;Sabella et al, 2014;Galeazzo et al, 2016). The latent variable of CI is evaluated in three dimensions: the company's strive for quality improvement (operationalized from Prajogo and Brown 2006, Sila (2007), and Näslund (2013)) and on-going elimination of nonvalue added activities (from Deming (1993) and Jurburg et al, (2015)) as well as process standardization (from Pellicer et al, (2012) and Romero et al (2015)).…”
Section: Soft and Hard Organizational Practicesmentioning
confidence: 99%
“…For a long-term effectiveness of improvement initiative, the organization needs to rigorously select projects that meet customers' needs (Jääskeläinen, Laihonen, & Lönnqvist, 2014); otherwise, failure to adopt a customer-focused approach may lead to deterioration of organizational performance. Organizations that identify projects based on their importance to the strategic priorities are more integrated and able to overcome unnecessary complexity (Galeazzo, Furlan, & Vinelli, 2016). Researchers emphasize the necessity of a unified coordination and goal setting of improvement initiatives and ascertain positive impact of project management on effectiveness of the improvement initiative (Gonzalez & Martins, 2016).…”
Section: Goal Setting and Project Managementmentioning
confidence: 99%
“…Thus, we argue that the organizations exercising goal setting and project management for improvement initiative would benefit from a higher level of process standardization. We adapt the mediator Goal Setting and Project Management from Galeazzo et al (2016), Kaynak (2003), Sabella, Kashou and Omran (2014).…”
Section: Goal Setting and Project Managementmentioning
confidence: 99%
“…A study by Galeazzo, Furlan, and Vinelli (2017) explored the key dimensions of organisational infrastructure, namely strategic alignment and team working, and their impact on sustaining a CI capability. They found that the ability to deploy business strategy into functional objectives and the strategic coordination of actions is critical to developing a CI capability.…”
Section: Developing a Process CI Capabilitymentioning
confidence: 99%
“…A commonly adopted approach to CI has been to implement ad hoc process improvement projects by simply applying established CI tools and techniques. Implementing such an approach is most likely to fail if the infrastructure needed to sustain a momentum of improvement has not been put in place (Anand et al 2009;Galeazzo, Furlan, and Vinelli 2017). Previously reported failure to do this may be attributable to the abstract nature of published guidelines on CI capability development (Garcia-Sabater, Marin-Garcia, and Perello-Marin 2012) and the lack of detail on the elements of a process for CI programme management.…”
mentioning
confidence: 99%